Strangle hernia in the children! not always, amyand hernia with appendicitis - M Lahfaoui; E Koulouris; A Alfaour; L Gouizi (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2020)
The diagnosis of acute appendicitis is sometimes difficult to make. Among the atypical presentations is Amyand's hernia. This is the development of acute appendicitis within an abdominal hernia. Amyand's hernia is a rare but important disease to know. This pathology bears the name of the English surgeon, Claudius Amyand, operator of the first appendectomy in the history of medicine in 1735, performed for an acute appendicitis inside an inguinal hernia. Here we present a case of Amyand's hernia in a 2-month-old male, who presented as a right-sided congenital hernia with pain in the right groin. He underwent herniotomy, which revealed that the hernia sac containing inflamed appendix. • Rare pathology • Very high risk of misdiagnosis: Strangulated hernia. • The knowledge of this pathology reduces the surprise effect which directly affects the results of the surgery and the postoperative follow-up. • The article allows to better know the ideal surgical management through a rich discussion (14 references).